A fully transparent, flexible PEDOT:PSS–ITO–Ag–ITO based microelectrode array for ECoG recording. Issue 6 (1st February 2021) - Yang, Weiyang; Gong, Yan; Yao, Cheng-You; Shrestha, Maheshwar; Jia, Yaoyao; Qiu, Zhen; Fan, Qi Hua; Weber, Arthur; Li, Wen
Abstract : Ultra-flexible, highly-conductive and fully-transparent μECoG electrode arrays made of PEDOT:PSS–ITO–Ag–ITO on thin parylene C successfully achieved neurophysiology recording. Abstract : Integrative neural interfaces combining neurophysiology and optogenetics with neural imaging provide numerous opportunities for neuroscientists to study the structure and function of neural circuits in the brain. Such a comprehensive interface demands miniature electrode arrays with high transparency, mechanical flexibility, electrical conductivity, and biocompatibility. Conventional transparent microelectrodes made of a single material, such as indium tin oxide (ITO), ultrathin metals, graphene and poly-(3, 4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT:PSS), hardly possess the desired combination of those properties. Herein, ultra-flexible, highly conductive and fully transparent microscale electrocorticogram (μECoG) electrode arrays made of a PEDOT:PSS–ITO–Ag–ITO assembly are constructed on thin parylene C films. The PEDOT:PSS–ITO–Ag–ITO assembly achieves a maximum ∼14% enhancement in light transmission over a broad spectrum (350–650 nm), a significant reduction in electrochemical impedance by 91.25%, and an increase in charge storage capacitance by 1229.78 μC cm −2 . Peeling, bending, and Young's modulus tests verify the enhanced mechanical flexibility and robustness of the multilayer assembly. The μECoG electrodes enable electrical recordings with high signal-to-noise ratios (SNRs) (∼35–36 dB) under different color photostimulations, suggesting that the electrodes are resilient to photon-induced artifacts. In vivo animal experiments confirm that our array can successfully record light-evoked ECoG oscillations from the primary visual cortex (V1) of an anesthetized rat.